2020
DOI: 10.1016/j.eucr.2019.101101
|View full text |Cite
|
Sign up to set email alerts
|

Giant bladder stone formed around sewing-needle in childhood: A case report and literature review

Abstract: We present cases of sewing needle as a nidus of the bladder stone in a seven-year-old girl admitted to the hospital with chief complaining burning micturition for 6 months. The Kidney, Ureter, and Bladder (KUB) X-ray revealed the bladder stone was 3.5 cm in length at the pelvic cavity and sewing needle in its center. The bladder stone was removed by open cystolithotomy without any complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…FB in the UB is uncommon[ 8 ], with few cases reported in pediatrics,[ 3 ] and usually result from iatrogenic injury, self-insertion for sexual gratification, or in psychiatric patients, and they can rarely migrate from adjacent organs, or following penetrating perineal trauma. [ 2 , 4 , 5 , 9 ] They also descend from the ureter or are formed as an encrustation over nonabsorbable suture material. [ 6 , 10 ] Self-insertion is rarely reported before puberty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FB in the UB is uncommon[ 8 ], with few cases reported in pediatrics,[ 3 ] and usually result from iatrogenic injury, self-insertion for sexual gratification, or in psychiatric patients, and they can rarely migrate from adjacent organs, or following penetrating perineal trauma. [ 2 , 4 , 5 , 9 ] They also descend from the ureter or are formed as an encrustation over nonabsorbable suture material. [ 6 , 10 ] Self-insertion is rarely reported before puberty.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] They can be self-inserted through the urethra, migrated from adjacent organs, as a complication of surgical procedure or instrumentation, or because of penetrating trauma. [ 4 - 6 ] Migration of FB to the UB from adjacent organs is rare, and it can penetrate from the Gastrointestinal tract (GIT) or Genitourinary (GU) tract [ 2 ]. The patient usually presents with urinary tract infection (UTI), dribbling, hematuria, dysuria, and sometimes urine retention.…”
Section: Introductionmentioning
confidence: 99%
“…Palinrungi MA et al reported a giant bladder stone in a seven-year-old girl formed around a sewing-needle. 4 Schwentner C and colleagues reported a two-year-old girl with a vesical giant cystine stone with a small atrophic left kidney. 5 In the current case, we report a rare case of a giant bladder stone with 72 × 42 × 44 mm in dimension and 152 gm in weight with recurrent UTI successfully managed with open cystolithotomy.…”
Section: Discussionmentioning
confidence: 99%
“…(Mohamed et al, 2021) reported a giant bladder stone with 152 grams and 7 cm in diameter (Mohamed et al, 2021). (Palinrungi et al, 2020) The disease is common in male children, with a male to female ratio of 10:1. Shockwave lithotripsy appears to offer a lower stone-free rate when compared with other procedures but has the shortest duration of hospital stay (Donaldson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%